The Efficacy of the Yasmin[Ethinylestradiol-Drospirenone (0.03/3 mg)] Treatment for Postoperative Abortion: A Protocol of Meta-Analysis - Tian, Tian; Feng, Huiyan; Liao, Xiaoqian; Su, Qiling; Li, Yunhui; Li, Xiaomao (Frontiers in Medicine, 2022)
Background Induced abortion is a universal phenomenon and about 25% of pregnancies in the world end in induced abortion. Induced abortion refers to the use of artificial or drug methods to terminate the pregnancy in the early stage of pregnancy, which is a remedy for failed contraception and accidental pregnancy. Induced abortion means surgical abortion. There are two commonly used methods: negative pressure suction abortion and forceps curettage for induced abortion. Abortion is invasive and it will cause great harm to women's reproductive function. Clinically, there are also cases of re-pregnancy within 3 months after abortion or even re-pregnancy without recovery of menstruation. To improve symptoms and reduce these complications, antibiotics, motherwort, and Yasmin[Ethinylestradiol-Drospirenone (0.03/3 mg)] are clinically used alone or in combination after induced abortion. Methods Data were collected from six databases, including three English databases of Cochrane Library, PubMed and Embase, and three Chinese databases of CNKI, Wanfang, and Weipu. The original indicators of vaginal bleeding, menstrual recovery time, bleeding time, endometrial thickness 21 days after surgery and so on were included, and the incidence of postoperative bleeding less than menstrual volume, menstrual re-fluid time ≤ 37 days, bleeding time ≤ 7 days, re-pregnancy without menstruation, re-pregnancy within 3 months after the operation, the total incidence of postoperative complications were based on the ratio of the number of events in the group to the total number of people in the group reported in the literature. Review Manager 5.4 software was downloaded from the Cochrane website to evaluate the quality of the literature and analyze the results using random or fixed-effects models. The outcome of index data is divided into two types, one is dichotomy, and the other is measurement data. The binary data is expressed by odds ratio (OR), and the measurement data is expressed by mean difference (MD), and the confidence interval of both is 95%. Results After completing this meta-analysis, the results will be available. Conclusion The results will provide reliable data basis for the value of Yasmin combined with antibiotics and Motherwort in postoperative induced abortion. PROSPERO Registration Number CRD42021246764.